Compartment syndrome in a neonate - Magdalena Santosa; Fatimah Indarso; Agus Harianto; Sylviati M. Damanik; Erwin Sarwono (Paediatrica Indonesiana, 2001)
A neonate born with severe asphyxia and considerable risk of infection was treated with intravenous sodium bicarbonate and intravenous antibiotics. At the age of five days he developed edema of the right forearm, tense on palpation, painful, hyperemic, and the hand was pallor, hypesthetic with maceration of the fifth finger. The diagnosis of compartment syndrome was established but it was delayed at least for about 48 hours. Decompression by fasciotomy using the volar Henry approach was performed; after which the pathologic changes rapidly subsided. Â The cause of this syndrome wasprobably due to intravenous sodium bicarbonate and repeated intravenous antibiotics. From this experience it is strongly emphasized that we have to be aware and able to diagnose compartment syndrome at the earliest possible time in severely ill neonates and children who have multiple intravenous injection. Daily inspection and careful evaluation of the condition at the site of the intravenous line will be very crucial to detect the syndrome.